A community of practice or a working psychological group? Group dynamics in core and peripheral community participation. Issue 4 (September 2018) - Gray, David E; Gabriel, Yiannis
The concept of communities of practice has become increasingly influential in management literature. Yet, many scholars regard the term as too homogeneous and lacking in empirical support. Our study explores the Silver Academy, a project involving over 100 unemployed and self-employed managers over the age of 50, who came together with the purpose of sharing knowledge and experience in starting up their own businesses. The study shows how the Academy matches the notion of community of practice, including mutual relationships, shared engagement and a common consensus of membership. However, applying Bion's theory of groups, we challenge the homogeneous and consensual notion of a community of practice, illustrating how, through unconscious group processes, some group members exhibit work-group mentality and the capacity for realistic hard work (and leadership), while others are caught in a basic-assumption mentality, prone to feelings of anxiety, guilt and depression. This is particularly so for a group that has gone through the recent trauma of unemployment.